VD_FINDINFO Décision / 2012 / 677 vom 30. November 2010 - VD Tribunal cantonal (2010)
LEX MITIOR, PROCURATION, RELIEF | 101 CPP, 129 al. 2 CPP (CH), 368 CPP (CH), 393 al. 1 let. b CPP (CH), 452 al. 2 CPP (CH)